Die betekenis en funksie van die himnes in Openbaring 12-22 - Viljoen, F. V. (Verbum et ecclesia, 2002)
The meaning and function of the hymns in Revelation 12-22 The hymns in Revelation 12-22 function as type of commentary, as they interpret the narrative events of the kernel plot. Being separated spatially and in some instances temporally, the hymns offer interpretations on the events and emphasise the basic themes of God’s accomplishment of salvation and judgement through Jesus Christ in the narrative. The final set of hymns in 19:1-8 recall the prior themes recounted through the hymns to form a musical climax. The hymns function as both prolepsis and analepsis in the narrative time, to the creation of the cosmos by God on the one hand, and the final victory of God on the other. As satellelites, the hymns maintain contact with the readers. The hymns function in an assuring sense throughout, constantly reminding of the final victory, one in which the implied reader plays an active role. A better understanding of the use of hymns in Revelation could enrich the use of songs in our liturgy today.